ASH DEPOSIT CHARACTERISTICS OF BLENDED COAL IN COAL COMBUSTION PROCESS - Ika Monika; Fahmi Sulistyohadi (Puslitbang tekMIRA, 2019)
Coal combustion process often occurs the problems in the reactor which is caused by fouling and slagging. One of the procedures to reduce the risk of fouling and slagging by blending the coal of Pendopo, Palangkaraya, Muara Enim and Samarinda, with the ratio of 25:75, 50:50, and 75:25. The ash deposit tendency is known by analyzing the composition and ash fusion temperature of coal, determining the ash type and calculating of the fouling and slagging. The results showed that the Pendopo and Palangkaraya coal with a ratio of 25:75 and 50:50 were classified as lignite with fouling and the slagging index was classified as a high and medium tendency. While the other blended coal was classified as a low and low-medium tendency.